Bone Mineral Density and Body Composition of Adult Premenopausal Women with Three Levels of Physical Activity - Fernando D. Saraví; Fabiana Sayegh (Journal of Osteoporosis)
Weight-bearing and resistance physical activities are recommended for osteoporosis prevention, but it is unclear whether an intensity level above current recommendations has a positive effect on adult premenopausal women. Body composition and bone mineral density (BMD) by DXA were compared in three groups of women as follows: Sedentary, Maintenance exercise, and federated Sport Team (n=16 for each group). Physical activity was estimated from the International Physical Activity Questionnaire (IPAQ). The groups did not differ in age, height, weight, or body mass index. Bone mineral content and non-fat soft tissue mass were higher and fat mass was lower in the Sport Team group than in the other groups. The same was true for BMD of total skeleton, lumbar spine, femoral neck, and total hip. A test for linear trend of body composition and BMD showed significant results when including all three groups. Simple and multiple regression analyses showed significant associations between physical activity level (or alternatively, years of participation in programmed physical activity) and bone mass measures at all sites except for the middle third of radius. It is concluded that a level of physical activity higher than that usually recommended benefits bone health in adult premenopausal women.